RANCANG BANGUN SISTEM PERINGATAN DINI PERGERAKAN TANAH MENGGUNAKAN MODUL NODEMCU DENGAN MIKROKONTROLER BERBASIS INTERNET OF THING - Danu, Asep; Nugroho, Yohanes Anton (Yayasan Education and Social Center, 2024)
This study discusses the design of a prototype landslide movement detector, to reduce or minimize the impact caused by landslides, especially in the district of Kulon Progo, Samigaluh district, Sidoharjo village. To make the design and implementation of the technology of the system of detection and early warning of disasters of land movement in real time. Through the VDI 2221 method, the study aims to create an effective tool in minimizing the impact of landslides and this innovative tool is expected to increase citizens' productivity.Based on the results of the research, the prototype process using soil moisture sensor, vibration sensor, and ESP32 cam is used as a sensor/reader module when there is a movement of the soil slide like the presence of indication of soil humidity the more moist with marked numbers confirmed through the telegram the smaller in the area where the device is used.All integrated sensors/modules use NodeMCU ESP8266 as a microcontroller that manages all inputs from the sensor/module output that generates information output and converts them into information outputs via a telegram, but before that happens, it must be ensured that the device is already configured with wifi or Internet network in operation.The tool is expected to function as desired and make a positive contribution to the people around it